Health care demand in the presence of discrete price changes - Michael Gerfin; Boris Kaiser; Christian Schmid (University of Bern, Department of Economics, 2014)
Deductibles in health insurance generate nonlinear budget sets and dynamic incentives. This paper uses detailed individual claims data from a large Swiss insurance company to estimate the response in health care demand to the discrete price increase that is generated by resetting the deductible at the start of each calendar year. We use a regression discontinuity type framework based on daily data to estimate the change in health care demand right before and right after the turn of the year. We find that for individuals with high deductibles health care demand drops by 27%, which translates into an elasticity of - . 21. The decrease is most pronounced for inpatient care and prescription drugs. By contrast, for individuals with low deductibles there is no significant change in health care demand (except for prescription drugs). A remaining open question is whether the observed behavioral responses can be attributed to intertemporal substitution or whether they constitute a classic moral hazard effect.
Keywords: C31; D12; I13; 330; health care demand; nonlinear pricing; dynamic incentives; health insurance